"It was definitely a sexual kind of sensation": sex, sexual identity, and gender in the phenomenology of psychosis. Issue 2 (3rd April 2018) - Jones, Nev; Rosen, Cherise; Kamens, Sarah; Shattell, Mona
ABSTRACT: Purpose: Over the past twenty years, few empirical studies have focused on manifestations of sex, sexual identity, and gender within the phenomenology of psychosis. The goal of the present analysis was to explore themes related to gender and sexuality among individuals diagnosed with a psychotic disorder. Methods: We conducted a qualitative analysis of 25 in-depth phenomenological interviews and a secondary analysis of two focus groups with an additional 24 participants (total N = 49), all of whom reported past or current treatment for a psychotic disorder. Results: Nearly three-quarters of interview participants and one quarter of focus group participants reported some kind of sex or gender-related content. Participants' experiences were grouped under the following four themes: "shame and persecution, " "sexual or sexualized violence, " "power, agency, sexuality & gender, " and "positive experiences of the erotic." Some participants described sexual experiences or content as a primary facet of their experiences, while for others it occupied a more secondary place. Many participants reported some degree of shame associated with sexual aspects of their experience. Conclusions: We emphasize the clinical importance of validating and engaging with sex/sexual themes, and call for future research focused on implications vis-a-vis engagement, treatment, and social recovery.